1983
DOI: 10.1093/carcin/4.8.997
|View full text |Cite
|
Sign up to set email alerts
|

Excision of aflatoxin B1-imidazole ring opened guanine adducts from DNA by formamidopyrimidine-DNA glycosylase

Abstract: This investigation has confirmed the earlier reports that when aflatoxin B1-DNA adducts are stored under physiological conditions some aflatoxin B1-guanine adducts are converted to a secondary product in which fission of the imidazole ring of the adduct guanine has occurred. Incubation of DNA containing aflatoxin B1-guanine adducts for an increasing number of hours under physiological conditions resulted in a progressive increase in the number of adducts in which the imidazole rings of guanines underwent fissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Finally, Fpg protein excised 8-hydroxyguanine residues from MB-light-treated calf thymus DNA (la). Therefore, Fpg protein and the 8-hydroxyguanine endonuclease recently described by Chung et al (14) (2,3,10,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Fpg protein excised 8-hydroxyguanine residues from MB-light-treated calf thymus DNA (la). Therefore, Fpg protein and the 8-hydroxyguanine endonuclease recently described by Chung et al (14) (2,3,10,12).…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme was shown also to liberate the imidazole ring-opened form of adenine residues from DNA treated with ionizing radiation (10) and of guanine residues modified at the N-7 position with bulky alkylating agents (12). The molecular cloning of the fpg+ gene of E. coli (8), the purification of the Fpg protein (9), and the isolation of a bacterial mutant defective in Fpg protein (4) were critical steps for studies of the biological significance of this protein.…”
mentioning
confidence: 99%
“…Subsequent work has shown that the glycosylase is active on a variety of modified ring-opened purines (9,12,14) and that the enzyme also has apurinic/apyrimidinic (AP) endonuclease (6, 39) and 5'-terminal deoxyribose phosphatase (21) activities. The AP endonuclease reaction proceeds via a 1-elimination reaction, resulting in a gap limited at the 3' and 5' ends by phosphoryl groups (6,39 .…”
Section: Mutmmentioning
confidence: 99%
“…AFB 1 -FAPY is less distortive to DNA architecture than is AFB 1 -N 7 -Gua, making AFB 1 -FAPY relatively resistant to repair (48); this is consistent with the observed persistence of AFB 1 -FAPY in vivo and with results of the present study, in which nuclear extracts from mouse lung and liver repaired AFB 1 -FAPY less effectively than AFB 1 -N 7 -Gua. Although evidence exists suggesting that enzymatic removal of AFB 1 -FAPY occurs by NER (50), bacterial FAPY-glycosylase has been shown to efficiently incise AFB 1 -FAPY lesions in vitro (35,51). FAPY-glycosylase is expressed in rodent cells (52), but the relevance of this pathway in mammalian repair has not been established.…”
Section: Discussionmentioning
confidence: 99%